Editöre Mektup - Red cell distribution width and contrast-induced nephropathy in patients who underwent primary percutaneous coronary intervention - Somsri Wiwanitkit; Viroj Wiwanitkit (Türk Kardiyoloji Derneği Arşivi, 2016)
red cell distribution width and contrast-induced nephropathy in patients underwent primary percutaneous coronary intervention red cell distribution width and contrast-induced nephropathy in patients underwent primary percutaneous coronary intervention red cell distribution width and contrast-induced nephropathy in patients underwent primary percutaneous coronary intervention